(untitled) (Scientific journal of the Fergana State University, 2023)
In this article the conditions for synthesis of polymermetallokomplexes contained different size of zinc oxide nanoparticles based on purified sodium-carboxymethylcellulose (Na-CMC) with degree of substitution DS=0,80-0,85 and degree of polymerization DP=950-1050 and zinc nitrate (Zn(NO3)2) solutions by chemical method at a temperature of 80 ⁰C were determined. Physicochemical properties of Na-CMC samples containing stable zinc oxide nanoparticles of various sizes and shapes were determined by IR-Fure spectroscopy, atomic force microscopy, X-ray diffractometric analysis.